Climate Governance in the Arctic - Koivurova, Timo; Keskitalo, E. Carina H.; Bankes, Nigel (Environment & Policy,, 2009)
Climate change is affecting the Arctic environment and ecosystems at an accelerating speed, twice the rate of the global average. This is opening the Arctic to transportation and resource development and creating serious challenges for local communities and indigenous peoples. Climate Governance in the Arctic considers two aspects of climate change from an institutional perspective. It focuses on how relevant regimes, institutions and governance systems support mitigation of climate change. It also examines the extent to which the varying governance arrangements in the Arctic support adaptation and the development of adaptation processes for the region. The book's focus on Arctic governance offers unique insights within climate change mitigation and adaptation research. Climate Governance in the Arctic is intended for an audience of international lawyers, international relations scholars and political scientists concerned with the regional implications of climate change for existing governance regimes and the role of indigenous peoples within those regimes.